Sin as a Tropos: The Ontology of Human Action in Maximus the Confessor - Mateiescu, Sebastian (2024)
One of Maximus the Confessor’s fundamental distinctions is that between logos and tropos. The former is being used by Maximus for explaining the rationality of creation as based in the divine Logos, while the latter is employed for the description of a set of non-essential properties which nevertheless remain enigmatic in their character. The nature of these tropoi-properties is often understood through negative terms as they are frequently described as making no part of the essence of beings, which is rather governed by the logoi of beings. This paper aims to overcome this explanatory gap by focusing on sin as a paradigmatic tropos-property in Maximus’s ontology. By taking its starting point in Maximus’s explicit exclusion of sin from the classical list of the categories of being, the argument focuses on Stoic philosophy as the closest theory to Maximus’s view on human action and evil. First, some key similarities between Maximus’s idea of tropos and the Stoic notion of use of the natural capacities of beings are identified in order to show the deep conceptual overlap between Maximus’s and the Stoic psychology of action. Second, the peculiar Stoic idea of having impulses towards predicates is further shown to correspond to Maximus’s idea of tropoi as properties obtainable about individuals through concrete volitional actions. In light of this interpretation, sin appears as a real property and yet a non-essential one. It is a causally driven Stoic-like predicate which results from the individuals’ modes of entering causal relations with God and with creation.